Passive macromodeling - Grivet-Talocia, Stefano, 1970-; Gustavsen, Bjørn, 1965- (John Wiley & Sons, Inc., 2016)
"In the first comprehensive treatment of passive macromodeling on the market, macromodeling experts Stefano Grivet-Talocia and Bjorn Gustavsen address the complex subject with examples of effective, proven methods. Finally, students and researchers may turn to a text that tends to the theoretical background essential to comprehending the algorithms' advantages and disadvantages. With the latest information on black-box passive macromodeling and software implementation, this book is a foolproof guide to both the basics and complexities of passive macromodeling"--